Jurusan Manajemen Fakultas Ekonomika dan Bisnis Universitas Diponegoro - Agusta, Sheila Rizkylia; Yuniawan, Ahyar (Diponegoro Journal of Management, 2014)
This research is titled “Analysis of the influence of Transformational Leadership, Compensation Satisfaction, and Organizational Commitment on Employee Performance ". The purpose  of  research  is to indentify  and  analyze  whether  organizational  commitment  have  aninfluence on the performance of employees at PT Perkebunan Nusantara IV (persero) Medan UnitKebun Pabatu.The population in this study were all employees of kantor MPC PT. Pos Indonesia cabang Semarang. Samples of this study are 66 employees. The hypothesis in this study is the transformational leadership, compensation satisfaction, and organizational commitment has positive and significant on employee performance.The  results  showed  that  there  is  a  positive  and  significant  correlation  betweenTransformational Leadership, Compensation Satisfaction, and Organizational Commitment on Employee Performance in kantor MPC PT. Pos Indonesia cabang Semarang 56,3% means that employees performance variables in this study can be explained by the variable of transformational leadership, compensation satisfaction, and organizational commitment of 56,3 %.